2015
DOI: 10.1016/j.jclepro.2014.09.049
|View full text |Cite
|
Sign up to set email alerts
|

Fostering the incorporation of sustainable development in higher education. Lessons learned from a change management perspective

Abstract: Fostering the incorporation of sustainable development in higher education. Lessons learned from a change management perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
223
1
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(240 citation statements)
references
References 48 publications
(79 reference statements)
4
223
1
12
Order By: Relevance
“…The challenges are related to logistics, students, and faculty. Perhaps the most critical factor is resistance from faculty and staff to change, which is directly linked to failure (Verhulst & Lambrechts, 2015). Acknowledging these challenges ahead of time and developing a plan to prevent and overcome them will make the implementation process more efficient.…”
Section: Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…The challenges are related to logistics, students, and faculty. Perhaps the most critical factor is resistance from faculty and staff to change, which is directly linked to failure (Verhulst & Lambrechts, 2015). Acknowledging these challenges ahead of time and developing a plan to prevent and overcome them will make the implementation process more efficient.…”
Section: Challengesmentioning
confidence: 99%
“…As such, scholars have found that many of the limitations of SDE implementation are not necessarily unique to sustainability, but rather the organization's ability to execute the change. Providing proper resources and support to faculty and staff help to ease the incorporation of change (Verhulst & Lambrechts, 2015). found that although SDE for instructors is crucial for SDE into curriculum, there is a narrow utilization on staff training programs.…”
Section: Challengesmentioning
confidence: 99%
See 3 more Smart Citations